Assessing EU merger control through compensating efficiencies - Pauline Luise Affeldt; Tomaso Duso; Klaus Gugler; Joanna Piechucka (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Worldwide, the overwhelming majority of large horizontal mergers are cleared by antitrust authorities unconditionally. The presumption seems to be that efficiencies from these mergers are sizeable. We calculate the compensating efficiencies that would prevent a merger from harming consumers for 1,014 mergers affecting 12,325 antitrust markets scrutinized by the European Commission between 1990 and 2018. Compensating efficiencies seem too large to be achievable for many mergers. Barriers to entry and the number of firms active in the market are the most important factors determining their size. We highlight concerns about the Commission's merger enforcement being too lax.
Keywords: L19; L24; L40; K21; 330; Compensating efficiencies; Efficiency gains; Merger control; Concentration; Screens; HHI; Mergers; Unilateral Effects; Market Definition; Entry barriers